A Refined Conjugate Gradient Algorithm for Image Denoising - Aiwa, Faisal Falah; Hameed, Nasmah Jameel; Hassan, Basim A. (Statistics, Optimization & Information Computing, 2026)
The conjugate formula is often the major focus of research in the field of conjugate gradient approaches. The conjugate gradient approach is employed to address challenges encountered in the realm of image restoration. Through the application of a quadratic model, an innovative coefficient conjugate will be generated for the operation. The algorithms exhibit both local and global convergence along with descent characteristics. The numerical evaluations indicated that the recently formulated method significantly surpasses its predecessor. The newly established conjugate gradient approach demonstrates enhanced efficacy relative to the FR conjugate gradient methodology, which is regarded as the benchmark within the industry.